Implikasi Yuridis Penetapan Hakim Berkaitan Diversi yang Melanggar Ketentuan Undang-Undang Sistem Peradilan Pidana Anak - Endriyanti, Megah Novita; Aprilianda, Nurini; Madjid, Abdul (Jurnal Cakrawala Hukum, 2019)
This diversion is the process of resolving cases of violations of law that occur, namely by bringing together the victims and their families and the perpetrators as well as their families to sit together to discuss the settlement of cases in a family manner. Legislation on the juvenile justice system. To answer the purpose of the paper, normative legal research is used, using a legal approach used to examine the Child Criminal Justice System Act, while the case approach uses the determination of judges in the case of Children. The results of the study indicate that the juridical implication of the judgesâ€™ determination regarding diversion which violates the provisions of the law on juvenile criminal justice systems is that they can be canceled, which can still be carried out as long as no party submits a cancellation. This diversion effort is a manifestation of restorative justice which aims to avoid children from the judicial process. So when the diversion is successfully carried out and an agreement arises, it means that the goal of restorative justice has been achieved. How to cite item:Â Endriyanti, M., Aprilianda, N., & Madjid, A. (2019). Implikasi Yuridis Penetapan Hakim Berkaitan Diversi yang Melanggar Ketentuan Undang-Undang Sistem Peradilan Pidana Anak.Â Jurnal Cakrawala Hukum, 10(1), 58-68. doi:https://doi.org/10.26905/idjch.v10i1.2947